The sociology of the image in Latin America: History and methodologies of analysis based on Silvia Rivera Cusicanqui, Beatriz Sarlo and Nelly Richard - Peters, Tomás (2025)
This article examines the principal theoretical and methodological architectures underpinning the thought of Silvia Rivera Cusicanqui, Beatriz Sarlo, and Nelly Richard concerning the relationship between image and society. It undertakes a historical review and critical discussion of the image as a problem in Latin America—from the colonial period to the present—followed by an analysis of the key arguments each thinker has developed from her respective situated perspective in Bolivia, Argentina, and Chile. The article argues that these three intellectuals have crafted a mode of writing and reflection that exceeds the disciplinary boundaries of sociology and philosophy, venturing into dispersed, plastic, and residual terrains in pursuit of new concepts and problematics that engage the political, cultural, and affective becomings of the image. In doing so, the article seeks to contribute, from a Southern perspective, to the ongoing reconfiguration of analytical frameworks concerning the image in Latin American thought.